2020
DOI: 10.1111/pce.13914
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress in Marchantia polymorpha: Sensing and mechanisms underlying a dynamic response

Abstract: Sensing and response to high temperatures are crucial to prevent heat‐related damage and to preserve cellular and metabolic functions. The response to heat stress is a complex and coordinated process that involves several subcellular compartments and multi‐level regulatory networks that are synchronized to avoid cell damage while maintaining cellular homeostasis. In this review, we provide an insight into the most recent advances in elucidating the molecular mechanisms involved in heat stress sensing and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 147 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…Drought, salt and heat stress also activate osmotic responses which entail the production of heat-shock proteins, osmolytic proteins and osmolytes ( Hasanuzzaman et al., 2013 ; van Zelm et al., 2020 ), while nutrient and salinity stress trigger the synthesis of ion transporters ( van Zelm et al., 2020 ). Whether these stress responses are activated in M. polymorpha in an ethylene-dependent manner remains to be studied, but initial genomic and transcriptomic analyses of salt- and heat-stressed M. polymorpha plants revealed that genes involved in oxidative stress (ROS metabolism) were conserved and enriched ( Tanaka et al., 2018 ; Marchetti et al., 2021 ). Additionally, transcriptional changes in ethylene signaling genes have been observed under conditions of phosphate starvation in M. polymorpha ( Rico-Resendiz et al., 2021 ), although the phenotypic consequences remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought, salt and heat stress also activate osmotic responses which entail the production of heat-shock proteins, osmolytic proteins and osmolytes ( Hasanuzzaman et al., 2013 ; van Zelm et al., 2020 ), while nutrient and salinity stress trigger the synthesis of ion transporters ( van Zelm et al., 2020 ). Whether these stress responses are activated in M. polymorpha in an ethylene-dependent manner remains to be studied, but initial genomic and transcriptomic analyses of salt- and heat-stressed M. polymorpha plants revealed that genes involved in oxidative stress (ROS metabolism) were conserved and enriched ( Tanaka et al., 2018 ; Marchetti et al., 2021 ). Additionally, transcriptional changes in ethylene signaling genes have been observed under conditions of phosphate starvation in M. polymorpha ( Rico-Resendiz et al., 2021 ), although the phenotypic consequences remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Charophycean algae also contain stress-related pathways that enable them to adapt to changing environmental conditions ( Holzinger et al., 2014 ; Hori et al., 2014 ; de Vries et al., 2018 ; de Vries et al., 2020 ). In M. polymorpha , tolerance to heat stress is linked to abscisic acid, jasmonic acid, and auxin signaling ( Marchetti et al., 2021 ), and coordination of growth and oxidative stress response in M. polymorpha involves the conserved DELLA transcription factor ( Hernández-García et al., 2021 ). Unraveling these stress response networks and their interaction with ethylene will be valuable for inferring which pathways may have been present in the ancestor of early land plants and for developing ways to mitigate the detrimental effects of abiotic stresses that are increasingly prevalent due to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings demonstrate that chloroplast-localised processes participate in cellular Ca 2+ signalling events. dependent regulation (Bánfi et al, 2004;Kimura et al, 2020;Marchetti et al, 2021).…”
Section: Symplastic Signallingmentioning
confidence: 99%
“…ROS and Ca 2+ signalling pathways are linked in the regulation of lipid accumulation in response to a combination of nitrogen limitation and oxidative stress in Chlorella sorokiniana (Liufu et al, 2023). The two RBOH isoforms in Marchantia polymorpha have conserved C‐terminal phosphorylation sites, which may serve as sites of Ca 2+ ‐dependent regulation (Bánfi et al, 2004; Kimura et al, 2020; Marchetti et al, 2021).…”
Section: Organellar Signalling Systemsmentioning
confidence: 99%
“…Guihur, Fauvet, Finka, Quadroni, and Goloubinoff (2021) found that a number of heat‐related mechanisms, such as acquired thermotolerance and accumulation of heat shock proteins are present in the moss Physcomitrium patens . Even the liverwort Marchantia polymorpha has a significant number of genes recognized as related to heat tolerance in angiosperms (Marchetti et al, 2021).…”
Section: Heat Stress Effects On Non‐vascular Plantsmentioning
confidence: 99%